2003
DOI: 10.1097/01.ccm.0000065271.23556.ff
|View full text |Cite
|
Sign up to set email alerts
|

Effects of albumin and Ringer’s lactate on production of lung cytokines and hydrogen peroxide after resuscitated hemorrhage and endotoxemia in rats

Abstract: We conclude that resuscitation with albumin may have utility in reducing ventilator-induced lung injury after hemorrhagic shock, but not after endotoxic shock. These findings suggest that the mechanisms leading to ventilator-induced lung injury after hemorrhage differ from those after endotoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 42 publications
1
29
0
5
Order By: Relevance
“…These three clinically available parameters were used to test the effectiveness of volume expansion and tissue perfusion with different resuscitation fluids, and the difference in gas exchange or in lung edema formation. The results are consistent with several reports on the protective effects of albumin on I/R-induced organ dysfunction (Boura et al, 2003;Zhang et al, 2003;Su et al, 2007).…”
Section: Nf-κb P65 Activation Following T/hs Induction and Albumin Trsupporting
confidence: 82%
“…These three clinically available parameters were used to test the effectiveness of volume expansion and tissue perfusion with different resuscitation fluids, and the difference in gas exchange or in lung edema formation. The results are consistent with several reports on the protective effects of albumin on I/R-induced organ dysfunction (Boura et al, 2003;Zhang et al, 2003;Su et al, 2007).…”
Section: Nf-κb P65 Activation Following T/hs Induction and Albumin Trsupporting
confidence: 82%
“…Studies in various animal models for acute ischemic organ damage have shown the protective effects of NO-Alb and PNA in treatment of ischemia-reperfusion tissue injury (28,31,40,43). In the present study, we examined the effects of NO-Alb on the acute lung injury induced by hypoxia-reoxygenation in transgenic sickle cell SAD mice.…”
Section: Discussionmentioning
confidence: 99%
“…The method measures the total oxidative potential with the exception of O 2 − since this radical appears to be unable to oxidize DCFH directly (Zhu et al 1994). In contrast, in studies attempting to assess pulmonary oxidative stress, only hydrogen peroxide was measured either in BAL fluid (Zhang et al 2003;Xu et al 2004) or in breath condensate (Zuckerbraun et al 2005). Interestingly, the results from our study showed that the generation of ROS derives mainly from PMNs cells despite that macrophages are the dominant cells in the BAL fluid.…”
Section: Discussionmentioning
confidence: 99%
“…With few exceptions (Zhang et al 2003), in the case of ALI, ROS and cytokines have not been measured in combination at the site of their production, namely in the BAL fluid. Besides, the current study is the first one that investigates the biological oxidative and inflammatory pulmonary loads in relation to lung morphologic changes that follow resuscitation from hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation